2013
DOI: 10.1016/j.biomaterials.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of intimal hyperplasia in injured rat arteries promoted by catheter balloons coated with polyelectrolyte multilayers that contain plasmid DNA encoding PKCδ

Abstract: New therapeutic approaches that eliminate or reduce the occurrence of intimal hyperplasia following balloon angioplasty could improve the efficacy of vascular interventions and improve the quality of life of patients suffering from vascular diseases. Here, we report that treatment of arteries using catheter balloons coated with thin polyelectrolyte-based films (‘polyelectrolyte multilayers’, PEMs) can substantially reduce intimal hyperplasia in an in vivo rat model of vascular injury. We used a layer-by-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 60 publications
0
42
0
Order By: Relevance
“…The high levels of circumferential gene expression observed in our past studies on balloon-transfer in rats likely resulted from the fact that, in those experiments, film-coated balloons were expanded and left in direct contact with injured tissue for 20 minutes. 46,47 In contrast, the balloons used in stent-mediated experiments in this current study were inflated for only 15–20 seconds prior to deflation and removal. In addition, we note that the arterial tissue of rats is significantly thinner than that of pigs, and the tissue treated in those past experiments was balloon-injured prior to experiment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high levels of circumferential gene expression observed in our past studies on balloon-transfer in rats likely resulted from the fact that, in those experiments, film-coated balloons were expanded and left in direct contact with injured tissue for 20 minutes. 46,47 In contrast, the balloons used in stent-mediated experiments in this current study were inflated for only 15–20 seconds prior to deflation and removal. In addition, we note that the arterial tissue of rats is significantly thinner than that of pigs, and the tissue treated in those past experiments was balloon-injured prior to experiment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we note that the arterial tissue of rats is significantly thinner than that of pigs, and the tissue treated in those past experiments was balloon-injured prior to experiment. 46,47 In a broader context, we note that layer-by-layer assembly is also very well suited for coating the surfaces of expanded stents 34 that could subsequently be crimped onto bare balloon assemblies after fabrication. This approach, while technically straightforward, was not adopted here to minimize potential influences that crimping procedures could have on the structures or behaviors of the films used in these proof-of-concept experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capability of controlled nucleic acid delivery has also been demonstrated in biomedical devices such as stents [89,90], and there are many additional areas where localized release will be of interest, including the control of fibrotic disorders and inflammatory or autoimmune response to implanted organs. We have already shown the potential of this kind of approach in the delivery of siRNA directly to tissue in a localized manner as a means of addressing tissue engineering or wound healing, and in the implementation of siRNA in targeted nanoparticles and DNA for transdermal vaccines.…”
Section: Conclusion and Perspective On Future Directionsmentioning
confidence: 99%
“…Following TCDD treatment, protein kinase C-delta (PKCδ) is activated in ovarian surface epithelial cancer cells, suggesting a potential intracellular role for PKCδ as an effector molecule for TCDD-mediated biological events in this ovarian cancer (46). PKCδ and its downstream target have been identified as critical factors mediating vascular injury response, such as intimal hyperplasia and aneurysm (47)(48)(49)(50)(51). Ren and colleagues reported that activated PKCδ increases production of pro-inflammatory chemokines through cytosolic interaction with the NF-κB subunit p65 (50).…”
Section: Treatment Of Ovarian Cancermentioning
confidence: 99%